Peningkatan Pengetahuan Pendidikan Lingkungan dan Konservasi Siswa/Siswi SDN Tumbang Nusa 2 di Desa Taruna Jaya - Mariaty Mariaty; Ise Afitah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This program's main objective is to instill character education in loving the environment in children, improve thinking skills, and increase children's creativity. The relationship between children and their surroundings is an important foundation for building a good relationship between humans and nature. Community service activities at SDN Tumbang Nusa 2, located in Taruna Jaya Village, Jabiren Raya, Pulang Pisau, Central Kalimantan, were held from July to August 2019. Activities carried out included counseling on environmental education and film screenings. It provides education to school-age children in knowing the environment, managing the environment, and increasing children's creativity in environmental conservation and forest conservation efforts. The implementation of the activity is the introduction of several types of plants that function as cover crops and good tree planting practices and provide training in making goods from used materials. The methods used are counseling, demonstrations, and mentoring. In this case, partners are school children who will have an understanding of environmental education and conservation, starting from the understanding of the environment, the causes of environmental damage, how to manage the environment around schools, and how to anticipate environmental damage. Besides, partners were also given knowledge of planting and caring for trees properly in the school environment. Partners were also given skills to make crafts from used goods, such as making flowers and leaves from plastic bags, making flower pots from used plastic drink bottles, and make a bicycle from cardboard.